Improving Engineering Knowledge by Promoting Collaboration between Universities and International Companies in Developing Countries - Zainab S. Al-Khafaji; Nabba S. Radhi; Mustafa S. Abdulraheem (International Journal of Engineering Education, 2020)
Several fields today are mainly dependent on cooperation among the different parties, and the education system one of these fields. Many agreements between local laboratories and local and international companies must be agreed. These agreements will be an initial stage in building corporation among the industrial community. However, these agreements should not remain on paper, and such partnership agreements should promote economic growth, social justice, protection of the environment and universal responsibilities during solving logistic and industry issues. Where in a country like Iraq which suffering from lack of job opportunities and the weakness of laboratories that lead to delay the education process. However, the partnership could include practical and scientific studies and then applying the research results in solving the real industry issues. This paper will discuss the effect of industrial partnership with the importance of engineering education and expectations for the accomplishment of new strategies and scenarios in the developing countries.